Over the Counter Sale of Antibiotics at Drug Stores Found in Mizan-Aman Town, Southwest Ethiopia: A Cross-Sectional Simulated Client Visit Study. (7th April 2019) - Damisie, Getahun; Hambisa, Solomon; Yimam, Mohammed
Abstract : Background . Antibiotics are crucial drugs, particularly in the developing world, where infectious diseases are a common cause of death. Misuse and overuse of antibiotics have driven the emergency of antibiotic-resistant bacteria, which in turn leads to a loss of efficacy of these drugs. This study aimed to assess the professional practice on OTC sale of antibiotics at community drug retail outlets found in Mizan-Aman town. Methods . A cross-sectional simulated client visit study was conducted among community drug retail outlets found in Mizan-Aman town, Southwest Ethiopia, from 14 to 28 March, 2018. Currently, there are 18 commercially licensed community drug retail outlets in Mizan-Aman town and the study was undertaken on all drug retail outlets. Each drug retail outlet was visited once by investigators who simulated inflicting clinical scenario according to simulated client method pharmacy surveys. Three different clinical scenarios were chosen and, in each of the three cases, three levels of demand were used to obtain the antibiotic. The findings of the study were entered, cleared, coded, and stored into Epi Info version 3.5.1 and exported to Statistical Package for Social Sciences (Windows version 21) and the collected data were compiled and presented as descriptive statistics using tables and figures. Results . Most, 17 (94.4%), of drug stores out of the total 18 in which all three clinical scenarios were allotted were issued antibiotics without a need of medical prescription with three different levels of demands. Antibiotics were sold without a prescription in most (94.4%) of drug stores in which a urinary tract infection clinical scenario was presented. Similarly, antibiotics were obtained without a prescription for acute diarrhea from 16 (88.9%) drug stores. With respect to sore throat simulation, antimicrobial drugs were obtained without a prescription from 14 (77.8%) drug stores. Commonly dispensed antibiotics were Metronidazole (50.0%), Ciprofloxacin (38.9%), and Amoxicillin (71.4%) for acute diarrhea, urinary tract infection, and sore throat case scenarios, respectively. Only 1 drug store (5.5%) refused to dispense any kind of antibiotics. Conclusion . The results of this study demonstrate that nonprescription sales of antibiotics were highly pronounced in contrary to national guidelines regarding this practice. Most of antibiotics were dispensed without a prescription when the simulator asked any medication to alleviate his/her symptoms.